The Development of Trends and Themes of Polygamy in Islamic Law in the Contemporary World - Sadat, Anwar; Husain, Rahmin Talib; Ibrahim, Zumiyati Sanu; Yusuf, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Polygamy and Islam are significant topics to discuss along with the lack of research literature on polygamy in Islam in recent years. Therefore, this study aims to find out the current situation of research on polygamy in Islam supported by a bibliometric analysis of scientific publications indexed in the Scopus database. This study applied bibliometric analysis using VOSviewer software to visualize the results of previous studies on polygamy in Islam indexed in the Scopus database from 1982-2022. The findings of the bibliometric analysis showed that previous studies on polygamy in Islam based on the Scopus database indicated the tendency of rare attention of academics toward this topic. Therefore, in the future, such a topic has very broad opportunities that may focus on theoretical and empirical studies to improve science development. This article is the first study to discuss polygamy in Islam through a bibliometric analysis approach. Thus, it is expected that this study has implications for future research trends by paying attention to variables that are still rarely investigated by academics.